Interleukin 1 beta induces rapid phosphorylation and redistribution of talin: a possible mechanism for modulation of fibroblast focal adhesion. - Qwarnström, E E (1991)
The majority of interleukin 1 (IL-1) receptors in human fibroblasts has been shown to be localized at focal adhesions. This study describes rapid alterations caused by IL-1 beta/IL-1-receptor interaction at these sites. Fibroblast monolayers, incubated with IL-1 beta and prepared for electron microscopy, showed successive loss of cell-substratum contact and fewer and less-pronounced processes. Immunocytochemistry revealed loss and redistribution of the talin staining initially observed after 5-15 min of IL-1 beta incubation. Similarly, the cytoskeleton showed a decrease in staining and a disorganization starting from 15 to 30 min after IL-1 addition, whereas extracellular fibronectin appeared largely unaffected. Prelabeling with [32P]phosphate showed a 2- to 3-fold increase in the level of talin phosphorylation, peaking at 15 min. Phospho amino acid analyses revealed a higher level of serine and threonine phosphorylation. The data suggest that the action of IL-1 beta on fibroblasts may be partially mediated by direct phosphorylation of talin via activation of a protein serine/threonine kinase, leading to changes in transmembrane linkage proteins and the cytoskeleton. Such alterations at focal adhesions may provide a mechanism by which IL-1 can rapidly modulate cell-matrix interactions during inflammation and wound healing.